Comparative Analysis of 2 Techniques of Double-Gloving Protection During Arch Bar Placement for Intermaxillary Fixation - Gaujac, Cristiano; Ceccheti, Marcelo M.; Yonezaki, Frederico; Garcia Júnior, Idelmo Rangel [UNESP]; Peres, Maria Paula S. M. (Elsevier, 2007)
Purpose: This study was conducted to comparatively evaluate, in a prospective and randomized manner, 2 techniques for providing double-gloving protection during arch bar placement for intermaxillary fixation. Materials and Methods: A total of 42 consecutive patients in whom application of an Erich bar was indicated for intermaxillary fixation were equally divided into 2 groups. In group 1, 2 sterile surgical gloves were used; in group 2, a nonsterile disposable inner glove was used under a sterile surgical glove. Wilcoxon, Mann-Whitney, Kruskal-Wallis, and binomial statistical tests were used to analyze the findings. Results: A total of 103 perforations were found in the outer gloves (47 in group 1 and 56 in group 2), along with 5 perforations in inner gloves in both groups (α = .01). No significant statistical difference was found between groups in terms of inner glove perforations (α = .05). The nondominant hand presented with 70.9% of the perforations, statistically significant to 1%. Conclusions: Both double-gloving techniques were found to provide effective clinician protection. The use of a nonsterile disposable glove under the surgical glove is possible for less-invasive procedures, offering the same safety as using 2 sterile surgical gloves while decreasing operational costs. This method does not eliminate the need to change gloves when a perforation is suspected or noted during the surgery, however. © 2007 American Association of Oral and Maxillofacial Surgeons.
Keywords: alveolar bone; arch bar placement; clinical trial; controlled clinical trial; cost control; disposable equipment; double gloving technique; equipment design; glove perforation; iatrogenic disease; instrument sterilization; intermaxillary fixation; minimally invasive surgery; prospective study; protective equipment; randomized controlled trial; statistical analysis; surgical glove; surgical technique; Disease Transmission, Patient-to-Professional; Disease Transmission, Professional-to-Patient; Equipment Failure; Fracture Fixation, Internal; Gloves, Surgical; Infection Control; Maxilla; Motor Skills; Oral Surgical Procedures; Prospective Studies; Statistics, Nonparametric; Wounds, Stab